Deducing how tropical rhyssines (Hymenoptera, Ichneumonidae) mate from body measurements - Keronen Sanna; Sääksjärvi Ilari E; Hopkins Tapani (PENSOFT PUBLISHERS, 2022)
The biology of many Darwin wasp (Hymenoptera: Ichneumonidae) species is poorly known. Existing museum specimens can potentially be used to get information on e.g. how species live, what they eat, and what their life cycle is. One example of this is a 1991 study by Eggleton in which he measured some rhyssine (Ichneumonidae: Rhyssinae) species, and used the results to deduce how the species likely mate. We extend this work by measuring five tropical species. We found no evidence that the males of our species scramble for females before the females emerge, which matches what was hypothesised by Eggleton. Further measurements of more species would provide information on how other species mate, and field observations of mating rhyssines would help confirm that Eggleton's method for deducing rhyssine mating strategies gives true results.